Regeneration method of ammoxidation catalyst
By calcining, sonicating, impregnating and coating the deteriorated ammonia oxidation catalyst, the activity of the catalyst was successfully restored, the problems of decreasing catalyst activity and sticking were solved, and the long-term stable and efficient use of the catalyst was achieved.
Patent Information
- Application Number
- CN202311213816.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing ammonia oxidation catalysts have decreased activity and are prone to stickiness during use, resulting in catalyst failure and reaction efficiency reduction, and lack of effective regeneration methods.
The deteriorating catalyst is calcined in an oxygen atmosphere, then sonicated in an acid solution, and impregnated in a molybdenum-containing salt solution, followed by drying and coating of organic compounds, carbon nanofibers and pore-making agents, and finally multiple calcinations are performed to restore the catalyst activity.
Effectively restore the activity of the catalyst, so that it maintains stability and efficiency for a long time in later use, avoiding the problem of catalyst deactivation and stickiness.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a regeneration method for an ammonia oxidation catalyst. Background Art
[0002] Isophthalonitrile (IPN) is an important organic raw material for organic synthesis. Tetrachloroisophthalonitrile (i.e., thiophanate-methyl) synthesized from isophthalonitrile by chlorination is a high-efficiency, low-toxic, broad-spectrum fungicide. Metaphenylenediamine (MXDA) obtained from isophthalonitrile by hydrogenation is an epoxy resin curing agent with excellent performance, and is also a raw material for isocyanates and high-barrier nylon materials. Isophthalonitrile is also commonly used in the downstream production of polyester resins and polyester fibers. Due to the chemical activity of the aromatic nitrile cyanide, a series of fine chemical products can be synthesized through hydrolysis, hydrogenation, addition, condensation, polymerization, halogenation and other reactions. It is an important raw material for the manufacture of pesticides, medicines, dyes, fragrances, oils, fuel additives, etc.
[0003] In the process of preparing isophthalonitrile, the direct ammoxidation process of meta-xylene is the simplest and most economical method. In the ammoxidation reaction technology of aromatic hydrocarbons, V-series catalysts are the most common and effective catalytic system. In the early stage, simple vanadium components or vanadium components with a small amount of promoters were generally used. Their activity was too high, their selectivity was too poor, and the yield of aromatic nitrile was low. From the composition of recent catalysts, there are mainly three compositions: V-Sb, V-Cr, and Sb-Fe. Among them, the preparation method of V-Cr catalyst is simple and has good repeatability. It has high reaction activity for the ammoxidation of aromatic hydrocarbons, but its catalyst activity is too high, which is easy to cause deep oxidation and generate a large amount of CO2, CO, and HCN. At the same time, the catalyst has a strong decomposition ability for ammonia, which greatly increases the consumption of ammonia.
[0004] In the 1950s, Showa Denko of Japan developed a m-xylene ammoxidation fixed bed synthesis isophthalonitrile production technology. In the 1970s, Mitsubishi Gas of Japan and Badger of the United States cooperated to develop a fine particle fluidized bed isophthalonitrile industrial device, which was mainly used to produce isophenylene diisocyanate, and the production level of isophthalonitrile was improved. In the 1980s, Mitsubishi Gas of Japan launched four-component catalysts such as V-Cr-B-Mo and V-Cr-BP. The catalytic reaction performance was improved on the basis of the original three-component, but its reaction by-products, especially CO, CO2, were still high in production. In the 1990s, it announced the five-element catalyst system (EP0525367A1) of V-Cr-BP-Mo, which improved the production of reaction by-products and improved the yield of isophthalonitrile. However, the document pointed out that the catalyst raw material of expensive ammonium phosphomolybdate must be used to obtain a desired reaction result. The V-Sb / Al or Si catalyst prepared by BASF (CN113646065A) is prepared into a fixed bed catalyst by adding K, Fe and W, and the isophthalonitrile yield is 78.8%, but according to the disclosed preparation method, it is impossible to prepare a fluidized bed catalyst. The fluidized bed catalyst developed by Shanghai Petrochemical Research Institute (CN107282060B) is a V-Cr series, which does not contain Sb, and the isophthalonitrile yield is only 78.8%.
[0005] Looking at the basic composition of V-Cr catalysts, they are divided into ternary, quaternary and pentacyclic. The main reason for the deactivation of these catalysts is that the activity of the catalyst mainly depends on the content and ratio of vanadium, chromium, rare earth elements and alkali metal elements on the carrier. Since the reaction is carried out in a common fluidized bed reactor, the active components are easy to fall off, resulting in a decrease in the content of active components, causing the catalyst composition to deviate from the optimal ratio range, and with the increase of reaction time, the active components molybdenum and bismuth elements are enriched on the catalyst surface. Due to the high valence Mo 6+ Reduced to low-valent Mo 5+ Or Mo 4+ At the same time, the released hydrogen ions combine with the lattice oxygen and are decomposed into water through a series of reactions, making the catalyst sticky or even agglomerated. At the same time, a large amount of carbon deposits appear on the surface of the catalyst, resulting in a significant decrease in the specific surface area. The above phenomena all lead to a decrease in the activity of the catalyst.
[0006] For example, in Japanese Patent Tokusho 63-33903, the catalyst with reduced activity is taken out and supplemented with molybdenum component before being put into the reactor.
[0007] Patent CN1110193A adds a molybdenum compound containing ammonium ions to a catalyst with reduced activity, and obtains a regenerated catalyst by drying and calcining.
[0008] However, the activity of ammonia oxidation catalysts after regeneration in existing reports is relatively low. At the same time, it has been found that simply taking the above measures for deteriorated catalysts has defects. For example, when the untreated catalyst is impregnated to supplement the active components, the active components are mainly distributed on the catalyst surface due to the low specific surface area, and the active components will be lost more rapidly during further use; and after the deteriorated catalyst is treated at high temperature, the low-valent molybdenum component on the catalyst surface can be partially converted to a high-valent state, but under the reaction conditions containing ammonia, the high-valent Mo6+ quickly converts to the low-valent Mo5+ or Mo4+, and the non-sticky effect of the catalyst can only last for a short time.
[0009] Based on the above background, there is currently no effective method for regenerating oxidation catalysts that can effectively solve the problems of catalyst activity decline and stickiness. Summary of the invention
[0010] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for regenerating an ammoxidation catalyst. The activity of the deactivated catalyst is restored to a level close to that of a fresh catalyst, and the activity can be kept basically stable for a long time during the later use, and the catalyst is wear-resistant and non-sticky. The regenerated catalyst is used in the reaction of preparing aromatic nitriles by ammoxidation of aromatic hydrocarbons, especially in the ammoxidation of meta-xylene to prepare isophthalonitrile, and has excellent catalytic reaction activity and stability, high selectivity and high yield.
[0011] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0012] A method for regenerating an ammonia oxidation catalyst comprises the following steps:
[0013] 1) calcining the degraded ammonia oxidation catalyst in an oxygen atmosphere;
[0014] 2) subjecting the catalyst calcined in step 1) to ultrasonic treatment in an acid solution;
[0015] 3) impregnating the catalyst after ultrasonic treatment in step 2) in a solution containing a molybdenum salt;
[0016] 4) drying the material obtained in step 3);
[0017] 5) applying the mixed powder containing the organic compound, carbon nanofibers and pore-forming agent to the material obtained in step 4) by spraying the adhesive and rolling the ball;
[0018] 6) Drying and roasting the material obtained in step 5).
[0019] The catalyst to be regenerated (also called degraded ammoxidation catalyst) of the present invention comprises a carrier and active components mainly composed of vanadium and chromium, and may also include components such as rare earth elements and alkali metal elements, which together constitute effective active components of the catalyst. The carrier is one or more of molecular sieves, kaolin, diatomaceous earth, silicon dioxide and aluminum oxide. The corresponding fresh catalyst is mainly used for the ammoxidation of meta-xylene to prepare isophthalonitrile.
[0020] As a preferred embodiment, the fresh catalyst of the present invention has the following general formula (1):
[0021] V 1.0 Cr 1.0 Li 0.05 X a O b (1)
[0022] Wherein: X is at least one selected from manganese, calcium, barium, antimony, lead, iron, tungsten and molybdenum, preferably molybdenum;
[0023] The value range of a is 0.6 to 1.8, preferably 0.6 to 1.2;
[0024] b is the number of oxygen atoms required to satisfy the valence of each element in the catalyst.
[0025] The catalyst that needs to be regenerated in the method of the present invention (also known as a degraded ammonia oxidation catalyst) refers to a catalyst whose activity has decreased by more than 5% relative to the activity of a fresh catalyst, until the catalyst activity is so low that it is unacceptable in terms of economic cost, such as the conversion rate of meta-xylene drops from 90% to 60%.
[0026] In the method of the present invention, the calcination temperature in step (1) is 450-550°C and the calcination time is 1-5 hours. The catalyst with reduced activity is calcined at high temperature by oxygen to make molybdenum react with oxygen to produce molybdenum oxide, and a large amount of carbon deposits react with oxygen to produce carbon dioxide.
[0027] In the method of the present invention, the acid solution in step 2) is one or more of hydrochloric acid, nitric acid and acetic acid solutions; the amount of the acid solution used depends on the degree of catalyst deactivation, and the amount of the acid solution used should completely immerse the degraded catalyst, and the solute mass is 0.01 to 0.2 times the weight of the degraded catalyst.
[0028] In the method of the present invention, the frequency range of the ultrasonic wave in the ultrasonic treatment described in step 2) is 30 kHz to 50 kHz, and the treatment time is 0.1 to 2 hours.
[0029] In the method of the present invention, the molybdenum salt in step 3) is one or both of ammonium heptamolybdate and ammonium tetramolybdate, the amount of the molybdenum salt used is 0.2 to 0.8 times the weight of the degraded catalyst based on the mass of molybdenum, and the impregnation time is 0.5 to 8 hours.
[0030] In the method of the present invention, the organic matter in step 5) is pyromellitic dianhydride; the amount of pyromellitic dianhydride used is 0.01 to 0.05 times the weight of the degraded catalyst in terms of mass.
[0031] In the method of the present invention, the amount of carbon nanofiber used in step 5) is 0.01 to 0.05 times the total weight of the degraded catalyst by mass.
[0032] In the method of the present invention, the binder is selected from one or more of water, ethanol, methanol and polyol solution, preferably ethanol.
[0033] In the method of the present invention, the pore-forming agent is selected from one or more of gum arabic powder, hydroxypropyl cellulose, lignin, and polyvinyl pyrrolidone, preferably polyvinyl pyrrolidone, and the amount thereof is 1 to 8 wt% of the mass of the degraded catalyst; the pore-forming agent decomposes during the calcination process to form many nanometer-scale pores, which are helpful for the entry and exit of reactant and product molecules, thereby effectively improving the catalyst activity and inhibiting the deactivation of the catalyst.
[0034] In the method of the present invention, the calcination temperature in step 6) is 450-600° C. and the calcination time is 1-5 hours.
[0035] It has been found that after long-term use, the catalyst will be enriched with molybdenum elements and even agglomerated and sticky. Based on this, the present invention introduces pyromellitic anhydride, which can undergo a hydrolysis reaction with hydrogen ions to generate pyromellitic acid, thereby improving the problem of catalyst stickiness caused by the generation of water in the reaction; secondly, the large π bond contained in pyromellitic anhydride can form a conjugated system with the active components V and Cr while improving the ionic bond characteristics of the catalyst, inhibiting the deep oxidation reaction of the catalyst and improving the selectivity. The ammonia oxidation catalyst in the present invention belongs to a vanadium-based catalyst, and the surface oxygen properties of the catalyst have a great relationship with the catalytic reaction performance. It is necessary to provide active oxygen species to the reaction site. Since the waste catalyst is sticky, it is difficult to remove all molybdenum elements only by ultrasound. Therefore, by introducing oxygen and high-temperature roasting, the molybdenum elements on the surface and pores of the waste catalyst can be oxidized to molybdenum trioxide, and then ultrasonic treatment can be performed to completely remove the molybdenum element. By introducing oxygen, more active oxygen species can be provided to the catalyst. The regenerated catalyst obtained by the present invention not only restores its activity, but also can maintain its activity, stability, wear resistance and non-stickiness for a long time during the later use process.
[0036] The catalyst regenerated by the method of the present invention is used for the ammoxidation of meta-xylene to prepare isophthalonitrile, which can be carried out in a fluidized bed reactor.
[0037] The regenerated catalyst prepared by the method of the present invention is used for the ammoxidation reaction of m-xylene, ammonia and oxygen-containing gas.
[0038] A method for the ammoxidation of meta-xylene, comprising the following steps: feeding meta-xylene: ammonia: oxygen-containing gas (in terms of oxygen content) in a fluidized bed equipped with the regeneration catalyst of the present invention at a molar ratio of 1:2-13:10-50, preferably 1:5-10:20-43, at a reaction temperature of 330-480°C, preferably 380-420°C; at a reaction pressure of 0-0.05 MPaG, preferably 0.01-0.03 MPaG; at a catalyst mass space velocity of 0.03-0.1 h / min -1 , preferably 0.05~0.08h -1 .
[0039] The oxygen-containing gas of the present invention is one of air, a mixture of air and a diluent gas, and a mixture of molecular oxygen and a diluent gas. The diluent gas is a reaction-inert gas or a mixture thereof, preferably N2, CO2, etc.
[0040] In the method of the present invention, the raw materials of meta-xylene, ammonia and oxygen-containing gas are preheated and then mixed, and the preheating temperature is 20-40°C.
[0041] The catalyst regeneration method of the present invention can restore the activity of the catalyst to more than 95% of the activity of the fresh catalyst, and after being used for 500 hours, the activity remains basically unchanged and is not sticky. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the listed embodiments.
[0043] The reaction activity evaluation method is as follows: the reaction pipeline is insulated by heating, the temperature is maintained at 330-480°C, the reaction outlet gas is effectively collected by water absorption, and the product is analyzed by gas chromatography GC-2014, the analysis conditions are 10°C / min from 20°C to 150°C and maintained for 5 minutes, and 10°C / min to 250°C and maintained for 5 minutes. The conversion rate of meta-xylene and the selectivity of isophthalonitrile are calculated.
[0044] Preparation and evaluation of degraded catalysts
[0045] 245.02g of vanadium oxalate, 238g of chromium nitrate, 34.5g of lithium nitrate and 141.2g of ammonium heptamolybdate were weighed in sequence and added to 311.42ml of water and stirred to form a slurry. Then 550g of carrier was added and stirred at 90°C for 5h. After being fully impregnated, the catalyst was placed in an oven, dried at 100°C for 8h, taken out, and then calcined at 550°C for 4h in a nitrogen environment to obtain an ammonia oxidation catalyst. 830g of active catalyst was obtained.
[0046] X-ray fluorescence analysis (XRF) shows that the composition of each active component in the catalyst can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 0.8 O b (b is the number of oxygen atoms required to satisfy the valence of each element in the catalyst).
[0047] 100g of 30-60 mesh catalyst was loaded into a fluidized bed reactor, and a raw material mixed gas of m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio) was introduced, and the catalyst mass space velocity was 0.05h -1 The reaction temperature was controlled at 410°C and the reaction pressure was 0.01 MPaG. After 1000 hours of reaction, the reaction outlet gas was effectively captured. The product analysis was performed by gas chromatography. The selectivity of isophthalonitrile was 87% and the yield was 85%.
[0048] The fluidized bed catalyst is seriously agglomerated. The X-ray fluorescence analysis (XRF) of the deteriorated catalyst shows that the composition of each active component in the catalyst can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 0.4 O c (c is the number of oxygen atoms required to satisfy the valence of each element in the catalyst).
[0049] Example 1
[0050] 100 g of the above-mentioned deteriorated catalyst was used in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05 h -1 The reaction temperature was controlled at 410°C and the reaction was carried out at a normal pressure of 0.01 MPaG. After the reaction was carried out for 4 hours, the reaction outlet gas was effectively captured. The product analysis was performed by gas chromatography, and the selectivity of isophthalonitrile was 80% and the yield was 65%.
[0051] The catalyst was taken out and measured by scanning electron microscopy (Hitachi, model S-4800) to be microsphere particles with an average particle size of about 49 microns. X-ray fluorescence analysis (XRF) measured: V 1.0 Cr 1.0 Li 0.5 Mo 0.5 O b (b is the number of oxygen atoms required to satisfy the valence of each element in the catalyst).
[0052] The catalyst was placed in a muffle furnace with an O2 flow rate of 0.6NL / min and a temperature of 400°C for reaction for 4 hours. After being taken out, it was dispersed in 0.85L of a 0.1mol / L hydrochloric acid solution, and ultrasonicated for 10 minutes (Merritek Technology, model UC-6200, 40kHz). Then, it was added to 0.171L of a 0.5mol / L ammonium heptamolybdate solution and stirred at 90°C for 5 hours. After being fully impregnated, the catalyst was placed in an oven and dried at 100°C for 8 hours to obtain an initial regenerated catalyst. 1g PVP, 1g pyromellitic anhydride, and 1g carbon nanofiber were weighed and the mixed powder was rotary coated on the surface of the initial regenerated catalyst by adjusting the spray rate of ethanol in a rotary roller coater. After molding, it was dried at 100°C for 5 hours, and then calcined at 500°C for 1 hour to obtain a regenerated catalyst.
[0053] The composition of each active component in the catalyst measured by X-ray fluorescence analysis (XRF) can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 0.6 P 0.005 O b (P represents pyromellitic dianhydride, and b is the number of oxygen atoms required to satisfy the valence of each element of the catalyst).
[0054] The catalyst was placed in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05h -1 The reaction temperature was controlled at 410°C and the reaction was carried out at normal pressure of 0.01 MPaG. After 4 hours of reaction, the reaction outlet gas was effectively captured. The product analysis by gas chromatography showed that the selectivity of isophthalonitrile was 85% and the yield was 85%. After 500 hours of reaction, the selectivity of isophthalonitrile was 84% and the yield was 85%. The catalyst was taken out and no obvious agglomeration was observed.
[0055] Example 2
[0056] Weigh 100g of the above-mentioned deteriorated catalyst, place the catalyst in a muffle furnace with an O2 flow rate of 0.6NL / min and a temperature of 400°C for reaction for 4h, take out and disperse the catalyst in 1.37L of 0.1mol / L hydrochloric acid solution, ultrasonicate for 10min (Merritek Technology, model UC-6200, 40kHz), add 0.286L of 0.5mol / L ammonium heptamolybdate solution, and stir at 90°C for 5h. After sufficient impregnation, the catalyst is placed in an oven and dried at 100°C for 8h to obtain an initial regenerated catalyst. Weigh 5g PVP, 3g pyromellitic anhydride, and 3g carbon nanofibers in a rotary roller coater by adjusting the spray rate of ethanol to achieve mixed powder rotation coating on the surface of the initial regenerated catalyst. After molding, dry at 100°C for 5h, and then calcine at 500°C for 1h to obtain a regenerated catalyst.
[0057] The composition of each active component in the catalyst measured by X-ray fluorescence analysis (XRF) can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 1.0 P 0.014 O b (P represents pyromellitic dianhydride, and b is the number of oxygen atoms required to satisfy the valence of each element of the catalyst).
[0058] The catalyst was placed in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05h -1 The reaction temperature was controlled at 410°C and the reaction was carried out at a normal pressure of 0.01 MPaG. After 4 hours of reaction, the reaction outlet gas was effectively captured. The product analysis by gas chromatography showed that the selectivity of isophthalonitrile was 85.5% and the yield was 86.1%. After 500 hours of reaction, the selectivity of isophthalonitrile was 85% and the yield was 86%. The catalyst was taken out and no obvious agglomeration was observed.
[0059] Example 3
[0060] Weigh 100g of the above-mentioned deteriorated catalyst, place the catalyst in a muffle furnace with an O2 flow rate of 0.6NL / min and a temperature of 400°C for reaction for 4h, take out and disperse the catalyst in 2.74L of 0.1mol / L hydrochloric acid solution, ultrasonicate for 10min (Merritek Technology, model UC-6200, 40kHz), add 0.343L of 0.5mol / L ammonium heptamolybdate solution, and stir at 90°C for 5h. After sufficient impregnation, the catalyst is placed in an oven and dried at 100°C for 8h to obtain an initial regenerated catalyst. Weigh 8g PVP, 5g pyromellitic anhydride, and 5g carbon nanofibers in a rotary roller coater by adjusting the spray rate of ethanol to achieve mixed powder rotation coating on the surface of the initial regenerated catalyst. After molding, dry at 100°C for 5h, and then calcine at 500°C for 1h to obtain a regenerated catalyst.
[0061] The composition of each active component in the catalyst measured by X-ray fluorescence analysis (XRF) can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 1.2 P 0.069 O b (P represents pyromellitic dianhydride, and b is the number of oxygen atoms required to satisfy the valence of each element of the catalyst).
[0062] The catalyst was placed in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05h -1 The reaction temperature was controlled at 410°C and the reaction was carried out at a normal pressure of 0.01 MPaG. After 4 hours of reaction, the reaction outlet gas was effectively captured. The product analysis by gas chromatography showed that the selectivity of isophthalonitrile was 85% and the yield was 86%. After 500 hours of reaction, the selectivity of isophthalonitrile was 85% and the yield was 85.8%. The catalyst was taken out and no obvious agglomeration was observed.
[0063] Comparative Example 1
[0064] Weigh 100 g of the above-mentioned deteriorated catalyst for regeneration experiment, place the catalyst in a muffle furnace with an O2 flow rate of 0.6NL / min and a temperature of 400°C for reaction for 4 hours, take out the catalyst and disperse it in 0.171L of 0.5mol / L ammonium heptamolybdate solution, soak it for 4 hours, dry it at 90°C for 12 hours, and calcine it at 500°C for 1 hour to obtain a regenerated catalyst.
[0065] The composition of each active component in the catalyst measured by X-ray fluorescence analysis (XRF) can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 0.6 Ob (b is the number of oxygen atoms required to satisfy the valence of each element in the catalyst)
[0066] The catalyst was placed in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05h -1 The reaction temperature was controlled at 410°C and the reaction was carried out at a normal pressure of 0.01 MPaG. After 4 hours of reaction, the reaction outlet gas was effectively captured. The product analysis was performed by gas chromatography. The selectivity of isophthalonitrile was 83% and the yield was 81%. After 500 hours of reaction, the selectivity of isophthalonitrile was 81% and the yield was 64%. The catalyst was taken out and it was observed that the catalyst had obvious agglomeration.
[0067] Comparative Example 2
[0068] Weigh 100g of the above-mentioned deteriorated catalyst, place the catalyst in a muffle furnace with an O2 flow rate of 0.6NL / min and a temperature of 400°C for reaction for 4h, take out and disperse the catalyst in 0.27L of a 0.1mol / L hydrochloric acid solution, ultrasonicate for 10min (Merritek Technology, model UC-6200, 40kHz), add 0.171L of a 0.5mol / L ammonium heptamolybdate solution, and stir at 90°C for 5h. After sufficient impregnation, the catalyst is placed in an oven and dried at 100°C for 8h to obtain an initial regenerated catalyst. Weigh 1g of PVP and 1g of pyromellitic anhydride in a rotary roller coater by adjusting the spray rate of ethanol to achieve a mixed powder rotary coating on the surface of the initial regenerated catalyst. After molding, it is dried at 100°C for 5h, and then calcined at 500°C for 1h to obtain a regenerated catalyst.
[0069] Then the regenerated catalyst was obtained after calcination at 500 °C for 1 h.
[0070] The composition of each active component in the catalyst measured by X-ray fluorescence analysis (XRF) can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 0.6 O b (b is the number of oxygen atoms required to satisfy the valence of each element in the catalyst)
[0071] The catalyst was placed in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05h -1The reaction temperature was controlled at 410°C and the reaction was carried out at a normal pressure of 0.01 MPaG. After 4 hours of reaction, the reaction outlet gas was effectively captured. The product analysis by gas chromatography showed that the selectivity of isophthalonitrile was 84% and the yield was 81.5%. After 500 hours of reaction, the selectivity of isophthalonitrile was 82% and the yield was 68%. The catalyst was taken out and obvious agglomeration of the catalyst was observed.
[0072] Comparative Example 3
[0073] Weigh 100g of the above-mentioned deteriorated catalyst, place the catalyst in a muffle furnace with an O2 flow rate of 0.6NL / min and a temperature of 400°C for reaction for 4h, take it out and disperse it in 0.85L of a 0.1mol / L hydrochloric acid solution, ultrasonicate for 10min (Merritek Technology, model UC-6200, 40kHz), add 0.171L of a 0.5mol / L ammonium heptamolybdate solution, and stir at 90°C for 5h. After sufficient impregnation, the catalyst is placed in an oven and dried at 100°C for 8h to obtain an initial regenerated catalyst. Weigh 1g of PVP, 1g of acetic anhydride, and 1g of carbon nanofiber in a rotary roller coater by adjusting the spray rate of ethanol to achieve mixed powder rotation coating on the surface of the initial regenerated catalyst. After molding, it is dried at 100°C for 5h, and then calcined at 500°C for 1h to obtain a regenerated catalyst.
[0074] The composition of each active component in the catalyst measured by X-ray fluorescence analysis (XRF) can be expressed as: V 1.0 Cr 1.0 Li 0.5 Mo 0.6 Q 0.01 O b (Q represents acetic anhydride, b is the number of oxygen atoms required to satisfy the valence of each element of the catalyst)
[0075] The catalyst was placed in a fluidized bed reactor, and the raw material mixed gas was m-xylene: ammonia: air (in terms of oxygen content) = 1:8:40 (molar ratio), and the catalyst mass space velocity was 0.05h -1 The reaction temperature was controlled at 410°C and the reaction was carried out at a normal pressure of 0.01 MPaG. After 4 hours of reaction, the reaction outlet gas was effectively captured. The product analysis by gas chromatography showed that the selectivity of isophthalonitrile was 83% and the yield was 69%. After 500 hours of reaction, the selectivity of isophthalonitrile was 81% and the yield was 68%. When the catalyst was taken out, obvious agglomeration was observed.
[0076] It can be seen from the results of Comparative Examples 1, 2, and 3 that the simple impregnation and ultrasonic treatment methods for the deteriorated catalyst cannot effectively regenerate the catalyst, and the catalyst still shows obvious activity decline and stickiness during the later use. Therefore, the present invention solves the problem of catalyst stickiness caused by water generated in the catalyst reaction by adding pyromellitic dianhydride, inhibits the deep oxidation reaction of the catalyst and improves the catalyst selectivity, and at the same time adds a layer of inorganic non-metallic film on the catalyst surface by rolling coating to increase its wear resistance.
Claims
1. A method for regenerating an ammonia oxidation catalyst, comprising the following steps: 1) calcining the degraded ammonia oxidation catalyst in an oxygen atmosphere; 2) subjecting the catalyst calcined in step 1) to ultrasonic treatment in an acid solution; 3) impregnating the catalyst after ultrasonic treatment in step 2) in a solution containing a molybdenum salt; 4) drying the material obtained in step 3); 5) applying the mixed powder containing the organic compound, carbon nanofibers and pore-forming agent to the material obtained in step 4) by spraying the adhesive and rolling the ball; 6) Drying and roasting the material obtained in step 5).
2. The method according to claim 1, characterized in that The deteriorated ammoxidation catalyst is obtained by using a fresh catalyst for the ammoxidation of meta-xylene to prepare isophthalonitrile; the activity of the cracked ammoxidation catalyst decreases by more than 5% relative to that of the fresh catalyst.
3. The method according to claim 2, characterized in that The fresh catalyst has the following general formula (1): V 1.0 Cr 1.0 Li 0.05 X a About b (1) Wherein: X is at least one selected from manganese, calcium, barium, antimony, lead, iron, tungsten and molybdenum, preferably molybdenum; The value range of a is 0.6 to 1.8, preferably 0.6 to 1.2; b is the number of oxygen atoms required to satisfy the valence of each element in the catalyst.
4. The method according to claim 1, characterized in that: The calcination temperature in step (1) is between 450°C and 550°C, and the calcination time is between 1 and 5 hours.
5. The method according to claim 1, characterized in that The acid solution in step 2) is one or more of hydrochloric acid, nitric acid and acetic acid solutions, and the amount of the acid solution used is 0.01 to 0.2 times the total weight of the degraded ammonia oxidation catalyst based on the mass of its solute.
6. The method according to claim 1, characterized in that The molybdenum salt in step 3) is one or both of ammonium heptamolybdate and ammonium tetramolybdate, the amount of the molybdenum salt is 0.2 to 0.8 times the weight of the degraded ammonia oxidation catalyst based on the mass of molybdenum, and the impregnation time is 0.5 to 8 hours.
7. The method according to claim 1, characterized in that In step 5), the organic matter is pyromellitic anhydride; the amount of pyromellitic anhydride used is 0.01 to 0.05 times the weight of the degraded ammoxidation catalyst.
8. The method according to claim 1, characterized in that In the step 5), the amount of carbon nanofiber used is 0.01 to 0.05 times the total weight of the degraded ammonia oxidation catalyst by mass.
9. The method according to claim 1, characterized in that: The pore-forming agent is selected from one or more of gum arabic powder, hydroxypropyl cellulose, lignin and polyvinyl pyrrolidone, and its usage is 1-8wt% of the mass of the degraded ammonia oxidation catalyst.
10. The method according to claim 1, characterized in that The calcination temperature in step 6) is 450-600° C. and the calcination time is 1-5 hours.
Citation Information
Patent Citations
Acrylonitrile catalyst for ammonia oxidation process
CN107282060B
Selective ammonia oxidation catalyst
CN113646065A
Catalyst and process for producing nitrile compounds
EP0525367A1
Feeding mechanism for antenna
JP1988033903A